Characterization of Lactic Acid Bacteria Isolated from Soymilk and Its Growth in Soymilk By-product Medium for the Application in Soymilk Fermentation - Retnowati, Faizah Diah; Purwestri, Yekti Asih; Sine, Yuni (Journal of Tropical Biodiversity and Biotechnology, 2024)
The separation phase of soy-product manufacturing, especially of soymilk production, involves using the liquid portion of soy while disposing primarily of the solid portion, known as soymilk by-product (SMB). The improper disposal of SMB can contribute to environmental concerns. As SMB contains many beneficial nutrients, this could serve as a valuable culture medium for lactic acid bacteria (LAB), especially considering the expense of the standard de Man, Rogosa, and Sharpe (MRS) medium. This study aimed to isolate and identify LAB from soymilk through 16S rRNA sequencing, assess the potential of SMB as a culture medium for LAB, and ferment soymilk with LAB cultured from SMB to demonstrate the probiotic capacity. The research identified a potential LAB as Weissella confusa. Effective cultivation of LAB was demonstrated at 2% SMB concentration, although LAB cultured with MRS medium yielded a higher colony count. Furthermore, fermentation of soymilk by the LAB isolates from SMB exhibited a positive probiotic ability, reaching 5.5 × 109 CFU/mL, with a lactic acid content of 0.27%.